The effect of high-altitude hypoxia on the hemodynamics of the pulmonary circulation and the red blood indices of rats - Shandaulov, A.Kh.; Khamchiev, K.M.; Ramazanov, A.K.; Zhumadilov, S.S.; Zhomartova, G.Zh.; Ibraibekov, Zh.G.; Elshina, K.A. (Fundamental and Experimental Biology, 2019)
The article is devoted to the study of the reaction of the pulmonary circulation and the state of the blood in response to the prolonged (2.5 and 10 months) stay of rats at an altitude of 3200 m above sea level (Tien Shan, Tuya-Ashu Pass). As a result of the study it was found that thesystolic pressure in the pulmonary artery increased to 60 % by the 2-month period and was increased throughout the stay in the mountains, with a constant diastolic pressure. As a result, the pulse pressure increased, which indicates an increase in the rigidity of the vessels of the pulmonary artery basin as the main cause of an increase in systolic pressure. Impedance in the lung tissue significantly increased by 30 %, which indicates the restructuring of the pulmonary vessels as an expression of a kind of «autoregulation» described by Folkov for vessels of the systemic circulation. Blood indices indicate long-lasting mechanisms of adaptation to high altitude, an increase in hemoglobin content in red blood cells. The role of erythrocytes in the conditions of the Tien Shan Highlands, apparently, is not so significant, at least in earlier periods of stay in the mountains.